Technology and Learning Media in Islamic Religious Education - Zulkifli Zulkifli; Khumaini Rosadi; Agus Susanti; Erni Yusnita; Era Octafiona (Permata : Jurnal Pendidikan Agama Islam, 2024)
This study investigated publication and citation trends related to Islamic Religious Education learning technology and media from 2009 to 2024. The analysis showed an increase in the number of publications in 2020 and 2023, reflecting the high interest in this topic. It was found that research related to Islamic Education learning technology and media responds to the challenges of globalization and the development of information technology, with a focus on improving learning effectiveness and the integration of religious values in modern education. The research also highlighted active international cooperation, especially between Indonesia and Malaysia, in developing meaningful contributions in this domain. The network visualization analysis showed three main focuses of the research: teaching, student learning, and e-learning; the application of technology in Islamic Religious Education; and the integration of technology and multimedia in religious learning. Finally, the overlay visualization showed a trend towards new and innovative research, highlighting the importance of continuing to develop learning approaches that are responsive to the times. This research provides valuable insights into how technology can enrich Islamic religious learning and point new directions in the development of effective learning methods.Keyword : Islamic Religious Education, Technology, Learning Media